A bilingual advantage in memory capacity: Assessing the roles of proficiency, number of languages acquired and age of acquisition. (June 2021) - Durand López, Ezequiel M.
Aims and objectives: This study examines whether different types of bilingualism modulate memory capacity differently. More specifically, the study assesses the effects of age of acquisition, number of languages acquired and proficiency in the second language (L2) on phonological short-term memory, visuospatial memory and semantic memory. Design: Memory capacity was measured by means of three tasks: the digit span task (phonological short-term memory); the Corsi block task (visuospatial memory); and the word span task (semantic memory). Participants were divided into five groups based on the number of languages acquired, age of acquisition and proficiency: monolinguals, intermediate L2 learners, advanced L2 learners, simultaneous bilinguals and multilinguals. Data and analysis: Analyses of variance were used to analyze participants' scores for each of the memory tasks. Findings and conclusions: For the word span task, no significant differences were found among the groups, which supports the notion that semantic memory is language independent. Furthermore, intermediate and advanced L2 learners and multilinguals presented significantly higher phonological short-term memory spans compared to simultaneous bilinguals. Finally, intermediate L2 learners and multilinguals significantly outperformed monolinguals on visuospatial memory spans. Results suggest that L2 acquisition might strengthen both visuospatial and phonological short-term memory, which in turn tend to improve as L2 proficiency increases. Originality: While previous studies have provided evidence of a bilingual advantage in memory capacity, these studies have generally grouped different types of bilinguals together (e.g., L2 leaners and heritage speakers). This study takes a step forward by examining differences in memory capacity across different types of bilinguals and in comparison to their monolingual peers in order to better understand the cognitive effects of bilingualism. Significance and implications: When considering age of acquisition, number of languages acquired and proficiency as grouping factors, different effects of bilingualism on memory capacity can be observed. Future studies on this matter should include bilingual participants that are comparable with regard to the aforementioned variables.